The Effect of the Number of Injector Holes and Fuel Octane Number on Motorcycle Engine Exhaust Gas Emissions - Achmad Walid; Santoso Santoso; Khambali Khambali; Purwoko Purwoko (International Journal of Industrial Innovation and Mechanical Engineering, 2025)
An increase in the number of vehicles should also be accompanied by improvements in technology that can increase engine efficiency and at the same time reduce air pollution. This research aims to determine the effect of using variations in the number of holes in the injector and the octane number of the fuel on exhaust emissions in motorcycle engines. The research method uses experiments with descriptive analysis. The independent variable is the number of holes in the injector, 4, 6, and 8 and the octane number of 90, and 92. In the exhaust emissions testing process using engine speeds of 1000 rpm, 2000 rpm and 3000 rpm. The bound variable is the emission of carbon monoxide (CO) gas and hydrocarbon gas (HC). Data from CO and HC gas emission testing results at 1000 rpm are all still within the permitted limits. Furthermore, statistical analysis shows that there is an influence of the number of holes in the injector and the octane value of the fuel on CO and HC exhaust emissions and there is no interaction between the octane value variables and the number of injector holes on the CO and HC exhaust gas values. The best results are CO gas emissions = 0.55% and HC = 66 ppm when using a 6 holes injector (standard) and using fuel with an octane value of 92.